(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
This work presents for the first time the development, optimization and structural characterization of titanium dioxide (TiO2) nanoparticles reinforced poly(methyl methacrylate) (PMMA) nanocomposite functionalized with natural saffron dye belonging to Crocus sativus L. The goal was to create a new class of sustainable hybrid materials with improved multifunctional properties. Here, the composites were prepared by solution casting and dip-coating technique with various loading of TiO2 (0.2, 0.4, 0.6 g wt. %), and were studied with particular focus on its effects upon morphology, dispersion and interfacial interactions. The structural, chemical dimensions and crystallographic investigation of nanocomposites are carried out by XRD, ATR-FTIR and FESEM with Image J analysis of particles for determining nanoparticle dispersion. Results proved the presence of crystal anatase TiO2, amorphous PMMA phase, good interface bonding facilitated by saffron dye and homogeneous dispersion with slight agglomeration at higher loadings. The hence obtained findings are indicative of strong interfacial interaction. The average particle sizes show a dramatic decrease from around 45 nm at lower TiO2 contents to 10 nm, suggesting the natural dispersion of the dye. The addition of TiO2 enhanced its integrity and structure, saffron dye provided optical function as well as bio-function to this novel class of nanocomposite system for possible: opto-electronic, bio-medical coating and eco-friendly materials development.